The 'low-volume acetabulum': dysplasia in disguise. Issue 4 (16th October 2018) - Vahedi, Hamed; Alvand, Abtin; Kazemi, Seyed Morteza; Azboy, Ibrahim; Parvizi, Javad
ABSTRACT: Although there are well described radiological criteria for diagnosing DDH, our experience has highlighted that a new sub-category of hips exists in which the classic radiographic characteristics for DDH may be normal but the coverage of the femoral head is compromised. The purpose of this study was to validate a simple radiographic measurement method for calculating the depth of the acetabulum in order to detect individuals with 'low-volume' acetabuli and under-covered femoral heads. We identified 24 patients who were suspected of having low-volume acetabuli and compared their radiographs with those of 150 patients with non-dysplastic hips. The radiographic indices measured included the lateral center-edge (CE) angle, the anterior CE angle, the femoral neck-shaft angle, the extrusion index, integrity of the Shenton's line, the crossover sign, and ischial spine sign. We have developed a novel, but a simple method, named the 'coverage index' (CI) to identify the presence of a low-volume acetabulum on plain radiographs. Comparisons were made between the low-volume hips and the non-dysplastic hips. The radiographic parameters indicative of developmental dysplasia of the hip (DDH) were within normal limits in all patients with low-volume acetabuli and therefore these hips could not be classified as 'dysplastic' based on the traditional radiological parameters. There was no difference between the mean radius of the femoral head in two groups. The mean CI was significantly greater in the non-dysplastic group compared with the low-volume acetabula cohort (1.62 ± 0.117 in non-dysplastic group versus 1.07 ± 0.11 in low-volume hips) ( P  = 0.0001). Orthopaedic surgeons should be aware of a hip abnormality in which the femoral head coverage is deficient, yet all the conventional parameters for measuring coverage, including the center edge angle, are within normal limits. We have introduced a simple radiographic measurement method that may help surgeons identify these patients using the anteroposterior radiographs of the hip.